KONSEP PENDIDIKAN ANDRAGOGI DALAM AL-QURAN PERSPEKTIF PENDIDIKAN ISLAM - Komarudin Komarudin (Kuttab : Jurnal Ilmu Pendidikan Islam, 2022)
The main purpose of this article is to obtain information about Andragogy education in the perspective of the Qur'an. This article is a qualitative literature article using content analysis. The results of the article are obtained if the concept of andragogy education is art and teaching adults to learn, how to help adults repeat the learning needed to keep motivating the pedagogy of repeating learning, new learning to get new learning experiences. There are 4 basic assumptions in Andragogy education, which includes student concepts, experience, learning and learning. In conclusion, in the perspective of Islamic education, the concept of Andragogy education is a relevant learning method for adult learning according to the Qur'an and Sunnah, namely awareness strategies, practice methods and learning methods in the Prophet's Hadith.